Jawabanmu

2014-08-23T20:03:56+07:00
1.  27^{2x-3} =  \sqrt{ \frac{1}{3} }
 27^{2x-3} =  (\frac{1}{3} )^{ \frac{1}{2} }
3^{3(2x - 3)} =  3^{-1( \frac{1}{2}) }
3(2x - 3) = -1 (1/2)
⇔ 6x - 9 = -1/2
⇔ 6x = -1/2 + 9
⇔ 6x = 17/2
⇔ x = 17/2 : 6
⇔ x = 17/2 . 1/6
x = 17/16

2.  25^{3x-4} = 5 .  125^{x+1}
 5^{2(3x - 4)} =  5^{1}  .  5^{3(x + 1)}
⇔ 2(3x - 4) = 1 + 3(x + 1)
⇔ 6x - 8 = 1 + 3x + 3
⇔ 6x - 8 = 3x + 4
⇔ 6x - 3x = 4 + 8
⇔ 3x = 12
⇔ x = 12/3
x = 4

3.  9^{x-1}  \sqrt{3x} = \frac{1}{ 81^{x+1} }: 3^{2x}
 3^{2(x-1)} . 3^{ \frac{x}{2} } = 3^{-4(x+1)}: 3^{2x}
2(x-1)+ \frac{x}{2} =-4(x+1)-2x
2x-2+ \frac{x}{2} =-4x-4-2x
2x+4x+ \frac{x}{2} =-4+2
 \frac{13x}{2} =-2
13x = -4
x = -4/13
2 5 2